1997
DOI: 10.1021/jp963807f
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy Study of the Pressure-Dependent Structural and Frictional Properties of n-Alkanethiols on Gold

Abstract: Atomic force microscopy (AFM) has been used to study the effect of pressure on the structural and frictional properties of self-assembled monolayers of n-octadecanethiol on Au(111). Sharp microfabricated silicon nitride tips (tip radii 100-300 Å) were used. At low load, the periodicity of the thiol layer is imaged. At higher load, the layer is observed to become disordered. At a critical contact pressure of ∼2.3 GPa, a transition from the thiol overlayer to the Au(111) substrate periodicity is observed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
125
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(138 citation statements)
references
References 31 publications
12
125
1
Order By: Relevance
“…Friction was analysed as a function of load by means of a modified imaging technique already reported. 3,8 In this mode, only a line (30 or 50 nm long, depending on the surface topography) of the sample surface was scanned while the feedback was disconnected and a decreasing voltage was applied to the vertical piezo, i.e. in the z-direction.…”
Section: Chemical Characterizationmentioning
confidence: 99%
“…Friction was analysed as a function of load by means of a modified imaging technique already reported. 3,8 In this mode, only a line (30 or 50 nm long, depending on the surface topography) of the sample surface was scanned while the feedback was disconnected and a decreasing voltage was applied to the vertical piezo, i.e. in the z-direction.…”
Section: Chemical Characterizationmentioning
confidence: 99%
“…Surface force measurements indicated that the methyl terminal groups in alkylsilane and alkanethiol SAMs rotated to accommodate a terminal gauche distortion (Fig. 2a), while the molecules still retained their upright close-packed structure with a lattice periodicity under moderate pressures of a few tens of MPa [98,99]. As shown in Fig.…”
Section: Influence Of Surface Terminal Groupmentioning
confidence: 99%
“…The tilting of the alkyl chains was accompanied with increase in friction force due to the decrease in the binding energy of the alkyl chains when going from the upright interlocked position to the tilted configurations [99][100][101]. Rupture of the SAM structure occurred once the pressure exceeded a threshold value on the order of several GPa, causing the loss of lubrication effect [98,99].…”
Section: Influence Of Surface Terminal Groupmentioning
confidence: 99%
“…[13][14][15] Alkanethiols are the most commonly studied SAMs: 16 they are relatively easy to prepare, form well-ordered close-packed films, and have been extensively investigated for tribological (friction, wear and lubrication) performance. [17][18][19][20][21][22] Researchers have studied various factors affecting their tribological behavior such as chain length, 23,24 terminal group chemistry, 19,[25][26][27][28] pressure, 29 humidity, 30 packing density, 31 and temperature. 30,32 A powerful and robust means of tribological control involves "active" strategies characterized by reversible responses to external stimuli that produce desired changes in the tribological system (surface, lubricant or coating).…”
Section: Introductionmentioning
confidence: 99%